CrowdTone: Crowd-powered tone feedback and improvement system for emails - Vaish, Rajan; Monroy-Hernández, Andrés (2017)
In this paper, we present CrowdTone, a system designed to help people set the appropriate tone in their email communication. CrowdTone utilizes the context and content of an email message to identify and set the appropriate tone through a consensus-building process executed by crowd workers. We evaluated CrowdTone with 22 participants, who provided a total of 29 emails that they had received in the past, and ran them through CrowdTone. Participants and professional writers assessed the quality of improvements finding a substantial increase in the percentage of emails deemed "appropriate" or "very appropriate" - from 25% to more than 90% by recipients, and from 45% to 90% by professional writers. Additionally, the recipients' feedback indicated that more than 90% of the CrowdTone processed emails showed improvement.